Foreign Body Ingestion in Children - Ji Hyuk Lee (Korean Society of Gastrointestinal Endoscopy, 2018)
Foreign body (FB) ingestion in children is common and most children are observed to be between 6 months and 3 years of age. Although most FBs in the gastrointestinal tract pass spontaneously without complications, endoscopic or surgical removal may be required in a few children. Thus, FB ingestion presents a significant clinical difficulty in pediatric gastroenterological practice. Parameters that need to be considered regarding the timing of endoscopic removal of ingested FBs in children are the children's age or body weight, the clinical presentation, time lapse since ingestion, time of last meal, type as well as size and shape of the FB, and its current location in the gastrointestinal tract. Esophageal button batteries require emergency removal regardless of the presence of symptoms because they can cause serious complications. Coins, magnets, or sharp FBs in the esophagus should be removed within 2 hours in symptomatic and within 24 hours in asymptomatic children. Among those presenting with a single or multiple magnets and a metallic FB that have advanced beyond the stomach, symptomatic children need a consultation with a pediatric surgeon for surgery, and asymptomatic children may be followed with serial X-rays to assess progression. Sharp or pointed, and long or large and wide FBs located in the esophagus or stomach require endoscopic removal.